Formulation and In Vitro Characterization of Cellulose-Based Propranolol Hydrochloride Sustained Release Matrix Tablets - Aashish Khadka; Bhupendra Raj Giri; Rishiram Baral; Shailendra Shakya; Ashwinee Kumar Shrestha (BioChem)
Background/Objectives: Propranolol HCl (PPH), a nonselective beta-adrenergic receptor blocker, is employed as an anti-hypertensive, anti-anginal, anti-arrhythmic, and anti-migraine agent. Given its utility in chronic conditions, developing a sustained-release dosage form becomes imperative to optimize therapeutic outcomes while enhancing patient adherence and minimizing side effects. In this study, we employed a widely adopted matrix-based system to develop PPH sustained-release (PPH-SR) matrix tablets, ensuring the uniform dispersion of the drug within the polymeric matrix to regulate its release rate. Methods: Utilizing cellulose-based polymers, specifically HPMC K100M and ethyl cellulose (EC), as matrix formers, nine different formulations were prepared at varying drug-to-polymer ratios. We employed a wet granulation method, followed by compression of the dried granules, to fabricate round-shaped biconvex PPH-SR tablets. Results: Among these different formulations, formulation 2 (F2), comprising 40 mg PPH and 50 mg HPMC K100M (along with other excipients), showed excellent flowability, as evidenced by Carr’s index and angle of repose values of 12.50 and 28.50, respectively. Additionally, the mechanical properties of F2 tablets showed a hardness of 12.34 ± 0.91 KP, an average weight of 200.45 ± 1.87 mg, with a friability of 0.20%, and a content uniformity of 98.36%. Moreover, in vitro release characteristics of F2 tablets demonstrated a sustained-release behavior, with 94.3 ± 10.2% drug release over 24 h. A comparative analysis with marketed tablets yielded similarity and dissimilarity factors of 64 and 8, respectively. Furthermore, the release profile of F2 exhibited a high degree of linearity with the Korsmeyer–Peppas model (R2 of 0.977), showcasing its reliability and predictability. Conclusions: In essence, this in-house developed PPH sustained-release formulation can improve patient adherence, reduce side effects, and improve therapeutic outcomes. These results align with our objective of enhancing the therapeutic efficacy of PPH and affirm the broader relevance of innovative formulation strategies in addressing the challenges of chronic disease management.